2019
DOI: 10.1002/adom.201900213
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Upconversion Luminescence Modification Based on Photochromism in BaMgSiO4:Yb3+,Tb3+ Ceramics for Anti‐Counterfeiting Applications

Abstract: Reversible upconversion luminescence modification based on photochromism has received considerable interest due to its potential applications in optical storage and high‐sensitivity optical switches. However, stimulation‐induced bleaching by an external thermal field is generally used for photochromism‐induced reversible upconversion luminescence modification, which limits its practical application. In this work, a gray BaMgSiO4:Yb3+,Tb3+ ceramic is prepared, exhibiting the photochromism from gray to pink colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(65 citation statements)
references
References 48 publications
0
65
0
Order By: Relevance
“…Presently, the realization of concurrent upconversion (UC) and DS have been successfully utilized in anti‐counterfeiting based on the lanthanide‐based dopants. [ 6–9 ] The Eu‐doped down‐shift luminescent materials have been applied in the Euro banknotes, which enables the visible photoluminescence (PL) based on UV lamp excitation. Meanwhile, the Bank of China also introduced the Yb/Er‐doped UC phosphors in the banknotes as the counterfeiting technique, which emits the yellow UC luminescence by the irradiation of 980 nm laser.…”
Section: Figurementioning
confidence: 99%
“…Presently, the realization of concurrent upconversion (UC) and DS have been successfully utilized in anti‐counterfeiting based on the lanthanide‐based dopants. [ 6–9 ] The Eu‐doped down‐shift luminescent materials have been applied in the Euro banknotes, which enables the visible photoluminescence (PL) based on UV lamp excitation. Meanwhile, the Bank of China also introduced the Yb/Er‐doped UC phosphors in the banknotes as the counterfeiting technique, which emits the yellow UC luminescence by the irradiation of 980 nm laser.…”
Section: Figurementioning
confidence: 99%
“…Upconversion (UC) luminescence refers to the conversion of electromagnetic waves from long to short wavelengths through multi‐photon processes where the absorption of infrared (IR) photons leads to visible emission, which has attracted a lot of attention on the bioimaging, 3‐D color display, printing ink, state‐of‐the‐art lighting, solar cell, fingerprint acquisition, anti‐counterfeiting, and so on 1‐7 . Particularly, based on the measurement of temperature‐dependent UC luminescence intensity of two thermally coupled energy levels of trivalent rare earth (RE 3+ ) ions, the non‐contact optical temperature sensor by using the fluorescence intensity ratio (FIR) technique still keeps a research hotspot in recent years owing to its advantages of fast response, high sensitivity and resolution 8‐13 . Under consideration of UC luminescence and temperature sensing properties, the Er 3+ ion with a pair of thermally coupled energy levels ( 2 H 11/2 and 4 S 3/2 ) is often regarded as the one of the most important activator ions to obtain strong UC luminescence in visible range under excitation of IR radiation because of its abundant metastable energy levels and high luminescent quenching concentration; meanwhile, it is also desirable in developing optical temperature sensors 14‐17 …”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the BaMgSiO 4 :Bi 3+ ceramics may be available as an optical storage media. Previous investigations demonstrated that the optical storage dimension and density can be expanded by multiplexing the luminescence intensity through the adjustment of the excitation light power [7,8,58]. Fig.…”
Section: Fig 1a Presents the Xrd Patterns Of Bamgsiomentioning
confidence: 99%